Mono- and polynuclear Ferrocenyl-derived complexes: synthesis, characterisation and biological evaluation as antimycobacterial and antiplasmodial agents - Baartzes, Nadia (Department of Chemistry, 2016)
Ferrocene-containing precursors, vinylferrocene and (E)-4-vinylferrocenylbenzaldehyde were prepared, by a Wittig olefination reaction and Heck cross-coupling reaction, respectively. Mononuclear ferrocenyl-derived imino complexes were synthesised by Schiff-base condensation reactions of (E)-4-vinylferrocenylbenzaldehyde with various amines. This included the preparation of a silicon-containing derivative and its carbon analogue, to determine the effect of the lipophilic moiety on the biological activity. In addition, polynuclear ferrocenyl-derived imino complexes based on the tris(2-aminoethyl)amine scaffold and the polypropyleneimine (PPI) first- and second-generation scaffolds were also synthesised using Schiff-base chemistry. These polynuclear complexes were prepared using template chemical procedures to that of the mononuclear complexes. The corresponding mono- and polynuclear ferrocenyl-derived amino complexes were synthesised via reductive amination reactions from the (E)-4-vinylferrocenylbenzaldehyde. The imine moiety was hydrogenated in order to compare the effect on the biological activity. The imino and amino complexes were isolated in moderate to high yields. A second series of ferrocenyl complexes was also prepared incorporating a thiosemicarbazone moiety, as this is a known pharmacophore and may confer favourable properties in terms of biological activity as well as solubility. Methyl hydrazinecarbodithioate was synthesised and reacted with the previously synthesised (E)-4-vinylferrocenylbenzaldehyde by a Schiff-base condensation reaction to afford a ferrocenyl dithiocarbamate. The dithiocarbamate was reacted with various amines via nucleophilic substitution reactions to give mono- and polynuclear ferrocenylthiosemicarbazone complexes. These complexes were isolated in low to moderate yields.